Generative design in civil construction: a case study in Brazil - Oscar, Luiz Henrique; Cerqueira, Lucas Cecílio; Cunha, Pedro Henrique; Qualharini, Eduardo Linhares (Frontiers in Built Environment, 2023)
The civil construction industry has a significant role in the socioeconomic development of a country and seeks to understand the emerging technologies of computational resources, such as artificial intelligence, and those that are inserted into the design processes, which influence the construction quality. This work investigates generative design, an approach to projects aided by algorithms. Recent new breakthroughs related to generative design have the potential to drastically change the methods of construction. This article provides a new view of building construction. Thus, through exploratory research based on application examples and a case study, this study presents the innovative aspects of generative design for construction projects.